Resin composition and method for producing the same, and resin molding and method for producing the same

JP2025021050APending Publication Date: 2025-02-13MITSUBISHI CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023124749
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13

AI Technical Summary

Benefits of technology

【0024】 本発明によれば、メタクリル系樹脂の透明性を損なわずに、耐衝撃特性を向上させた樹脂組成物及び樹脂成形体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021050000001_ABST
    Figure 2025021050000001_ABST
Patent Text Reader

Abstract

To provide a resin composition, and a resin molding and a method for producing the same which can improve impact resistance without impairing transparency of a methacrylic resin.SOLUTION: A resin composition contains a methacrylic polymer (A) and an acrylic multilayer particle structure polymer (B), wherein the acrylic multilayer particle structure polymer (B) contains a solidified body of an acrylic multilayer particle structure polymer latex (C) which is emulsified and polymerized under the condition that the range of a pH is more than 9.0 and less than 14.0. A method for producing a resin composition includes: a polymerization step of emulsifying and polymerizing a substance under the condition that the range of a pH is more than 9.0 and less than 14.0, and obtaining an acrylic multilayer particle structure polymer latex (C); a solidification step of solidifying the obtained acrylic multilayer particle structure polymer latex (C), and obtaining the acrylic multilayer particle structure polymer (B); and a kneading step of kneading the obtained acrylic multilayer particle structure polymer (B) and the methacrylic polymer (A).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing an acrylic multilayer polymer and a method for producing the same, and to a resin molded article using the resin composition and a method for producing the same. [Background technology]

[0002] Methacrylic resins are excellent in weather resistance and transparency. Molded products for various applications can be manufactured by melt molding the methacrylic resins by injection molding, extrusion molding, compression molding, etc. However, since the impact resistance of the methacrylic resins is insufficient, cracks, chips, etc. may occur when the resins are subjected to impacts such as dropping, collision, and vibration. In order to improve the impact resistance of the methacrylic resins, it has been conventionally practiced to blend an elastic material into the methacrylic resins. For example, a technique is known in which an acrylic multilayer particle structure polymer obtained by solidifying an acrylic multilayer particle structure polymer latex obtained by emulsion polymerization is blended into the methacrylic resin.

[0003] However, when an acrylic multilayer particle structure polymer is kneaded with a methacrylic resin, the transparency inherent to the methacrylic resin is impaired, and the transparency of the resulting resin composition and the resin molded product obtained by molding the resin composition may become insufficient.

[0004] Patent Document 1 discloses that in order to provide a resin composition having improved impact resistance without impairing the transparency of the methacrylic resin, a specific inorganic fine powder is mixed in a specific amount with a powdered acrylic multilayer particle structure polymer and then blended with the methacrylic resin.

[0005] Patent Document 2 discloses a method for emulsion polymerization of vinyl monomers in the presence of at least one selected from hydroxides, carbonates and hydrogencarbonates of alkali metals or alkaline earth metals together with a phosphate salt so that the pH of the polymerization system is in the range of 6.0 to 9.0, and discloses that even if a multilayered acrylic elastomer obtained by coagulating a latex obtained by such a method is blended with a methacrylic resin, there is no problem in thermal decomposition or appearance after molding. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2007-23242 A [Patent Document 2] Japanese Patent Application Publication No. 63-221108 Summary of the Invention [Problem to be solved by the invention]

[0007] The resin composition obtained in Patent Document 1 has a problem in that the transparency of the resin composition is insufficient because the color of the inorganic fine powder itself affects the transparency of the resin composition. In Patent Document 2, emulsion polymerization is performed under conditions where the pH of the polymerization system is in the range of 6.0 to 9.0, so that the particle size distribution of the resulting acrylic multilayer structure polymer latex varies, and the resin composition obtained by blending this with a methacrylic resin has an insufficient effect of improving the transparency and impact resistance. In Patent Document 2, a phosphate ester salt is coexisted as an emulsifier in the emulsion polymerization, but the phosphate ester salt is not preferable from the viewpoint of deteriorating the appearance when the resin is molded into a resin product, since the phosphate remains in the multilayer particle structure polymer. In Reference Example 1 of Patent Document 1, in the emulsion polymerization for producing the multilayer particle structure polymer latex A, 236 parts of deionized water, 0.48 parts of SFS, 1.2×10 CF -4 Parts EDTA 3.6 x 10 -4In this case, when 0.02 part of sodium carbonate is added, the pH of the emulsion polymerization system is about 8.5 and does not exceed 9.0, so that it is not possible to obtain a monodisperse multilayer particle structure polymer with one peak in the particle size distribution.

[0008] Therefore, an object of the present invention is to provide a resin composition and a resin molded article having improved impact resistance without impairing the transparency of a methacrylic resin, and a method for producing the same. [Means for solving the problem]

[0009] As a result of extensive investigations aimed at solving the above-mentioned problems, the present inventors have found that when an acrylic multi-particle structure polymer (B) containing a coagulate of an acrylic multi-particle structure polymer latex (C) emulsion-polymerized under a pH range of more than 9.0 and less than 14.0 is blended with a methacrylic polymer (A), the inherent transparency of the methacrylic polymer (A) is maintained and the impact resistance can be improved, thereby solving the above-mentioned problems. That is, the present invention relates to the following.

[0010] [1] A resin composition comprising a methacrylic polymer (A) and an acrylic multilayer particle structure polymer (B), wherein the acrylic multilayer particle structure polymer (B) comprises a coagulated product of an acrylic multilayer particle structure polymer latex (C) emulsion-polymerized under a pH range of more than 9.0 and less than 14.0.

[0011] [2] The resin composition according to [1], wherein the particle size distribution of the acrylic multi-particle structure polymer in the acrylic multi-particle structure polymer latex (C) has one peak.

[0012] [3] The resin composition according to [1] or [2], wherein the acrylic multilayer particle structure polymer latex (C) contains at least one compound selected from the group consisting of hydroxides, carbonates, and hydrogencarbonates of alkali metals or alkaline earth metals.

[0013] [4] The resin composition according to [3], characterized in that the content of at least one compound selected from the group consisting of hydroxides, carbonates and hydrogencarbonates of alkali metals or alkaline earth metals is 0.03 to 1.0 parts by mass per 100 parts by mass of the solid content of the acrylic multilayer particle structure polymer latex (C).

[0014] [5] The resin composition according to [3] or [4], wherein the at least one compound selected from the group consisting of hydroxides, carbonates, and hydrogencarbonates of alkali metals or alkaline earth metals contains a hydrogencarbonate.

[0015] [6] The resin composition according to [5], wherein the hydrogen carbonate contains sodium carbonate.

[0016] [7] The resin composition according to any one of [1] to [6], wherein the methacrylic polymer (A) contains 50 mass % or more of repeating units derived from methyl methacrylate.

[0017] [8] A resin composition comprising a methacrylic polymer (A) and an acrylic multilayer particle structure polymer (B), wherein the acrylic multilayer particle structure polymer (B) has one peak in particle size distribution.

[0018] [9] A resin molded product obtained by molding the resin composition according to any one of [1] to [8].

[0019]

[10] An automobile component comprising the resin molded article according to [9].

[0020]

[11] A toy comprising the resin molding described in [9].

[0021]

[12] A component for home appliances, comprising the resin molded article described in

[10] .

[0022]

[13] A method for producing a resin composition, comprising: a polymerization step of obtaining an acrylic multi-particle structure polymer latex (C) by emulsion polymerization under conditions in which the pH is in the range of more than 9.0 and less than 14.0; a coagulation step of obtaining an acrylic multi-particle structure polymer (B) by coagulating the obtained acrylic multi-particle structure polymer latex (C); and a kneading step of kneading the obtained acrylic multi-particle structure polymer (B) with a methacrylic polymer (A).

[0023]

[14] A method for producing a resin molded product, comprising producing a resin composition by the method for producing a resin composition according to

[13] , and molding the resulting resin composition. Effect of the Invention

[0024] According to the present invention, it is possible to provide a resin composition and a resin molded article having improved impact resistance without impairing the transparency of the methacrylic resin. [Brief description of the drawings]

[0025] [Figure 1] 1 is a chart showing the particle size distribution of the acrylic multilayer particle structure polymer (B-1) in Example 1. [Diagram 2] 3 is a chart showing the particle size distribution of the acrylic multilayer particle structure polymer (B-2) in Example 2. [Diagram 3] 2 is a chart showing the particle size distribution of an acrylic multilayer particle structure polymer (B-3) in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The present invention will be described in detail below. However, the following description is an example of an embodiment of the present invention, and the present invention is not limited to the contents of the following description as long as it does not exceed the gist of the present invention. Unless otherwise specified, in this specification, a numerical range expressed with "~" means a range including the numerical values ​​before and after "~" as the lower and upper limits, and "X~Y" means equal to or greater than X and equal to or less than Y.

[0027] [Resin composition] A resin composition according to an embodiment of the present invention is a resin composition containing a methacrylic polymer (A) and an acrylic multilayer particle structure polymer (B), characterized in that the acrylic multilayer particle structure polymer (B) contains a coagulate of an acrylic multilayer particle structure polymer latex (C) emulsion-polymerized under a pH range of more than 9.0 and less than 14.0. It can be confirmed that the acrylic multilayer particle structure polymer latex (C) is obtained by emulsion polymerization by the presence of an emulsifier used in the emulsion polymerization in the acrylic multilayer particle structure polymer latex (C), and it can be confirmed that the acrylic multilayer particle structure polymer (B) is a coagulated product of such an acrylic multilayer particle structure polymer latex (C) by the presence of residual components of the emulsifier in the coagulated product.

[0028] The method for producing the resin composition of the present invention is not particularly limited, but a polymerization step of obtaining an acrylic multi-particle structure polymer latex (C) by emulsion polymerization under a pH range of more than 9.0 and less than 14.0; a coagulation step of coagulating the obtained acrylic multi-particle structure polymer latex (C) to obtain an acrylic multi-particle structure polymer (B); A kneading step of kneading the obtained acrylic multi-particle structure polymer (B) with the methacrylic polymer (A). It is preferable to produce the resin composition according to the method for producing the resin composition of the present invention, which comprises the steps of:

[0029] By undergoing the above polymerization step and coagulation step, it is possible to obtain an acrylic multilayer particle structure polymer (B) which is monodisperse with only one peak in the particle size distribution and has small variation in particle size. Therefore, a resin composition according to another embodiment of the present invention is a resin composition containing a methacrylic polymer (A) and an acrylic multilayer particle structure polymer (B), characterized in that the particle size distribution of the acrylic multilayer particle structure polymer (B) has one peak.

[0030] [Methacrylic polymer (A)] The resin composition according to the present embodiment contains the methacrylic polymer (A), and thus exhibits good transparency. In addition, decomposition due to heat or light is suppressed, and the resin composition exhibits good thermoformability, heat resistance, and mechanical strength.

[0031] In this specification, the methacrylic polymer (A) is a polymer containing repeating units derived from methyl methacrylate (MMA) (hereinafter also referred to as "MMA units"). The methacrylic polymer (A) is preferably a copolymer containing MMA units and repeating units derived from a vinyl monomer copolymerizable with MMA (hereinafter also simply referred to as "vinyl monomer") (hereinafter also referred to as "other vinyl monomer units"). In this specification, the term "repeating unit" refers to a unit derived from a monomer formed by polymerization of the monomer. The repeating unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by treating the polymer obtained by the polymerization reaction.

[0032] From the viewpoint of transparency and thermal stability of the resin composition, the content of MMA units is preferably 50 to 100 mass% and the content of other vinyl monomer units is preferably 0 to 50 mass% relative to the total mass of the methacrylic polymer (A). The lower limit of the content of MMA units is more preferably 60 mass% or more, even more preferably 70 mass% or more, particularly preferably 80 mass% or more, and most preferably 90 mass% or more. The upper limit of the content of other vinyl monomer units is more preferably 40 mass% or less, even more preferably 30 mass% or less, particularly preferably 20 mass% or less, and most preferably 10 mass% or less.

[0033] When the methacrylic polymer (A) is a copolymer, the sequence of the copolymer is not particularly limited and may be, for example, a random copolymer, a block copolymer, or an alternating copolymer, but is preferably a random copolymer.

[0034] Methyl methacrylate (MMA) used to produce the methacrylic polymer (A) can be produced by, for example, the acetone cyanohydrin method, the new acetone cyanohydrin method, the C4 direct oxidation method, the direct meth method, the ethylene method, the new ethylene method, etc. Furthermore, the MMA may be one produced by the C4 direct oxidation method using isobutanol derived from biomass as a starting material, or may be MMA obtained by chemically recycling methacrylic resin or acrylic resin waste materials.

[0035] When the methacrylic polymer (A) is a copolymer containing other vinyl monomer units, the vinyl monomer is preferably an acrylic acid ester or styrene. By containing such other vinyl monomer units in the methacrylic polymer (A), the thermal stability of the resulting resin composition is improved.

[0036] The acrylic acid ester is preferably an acrylic acid ester having an alkyl group having 1 to 6 carbon atoms in the side chain, and examples thereof include methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, and t-butyl acrylate. These may be used alone or in any ratio and combination of two or more. Among these, from the viewpoint of the thermal stability of the resin composition, at least one selected from the group consisting of methyl acrylate, ethyl acrylate, and n-butyl acrylate is preferred, and at least one selected from the group consisting of methyl acrylate and ethyl acrylate is more preferred.

[0037] The vinyl monomers can be used alone or in any combination of two or more kinds in any ratio.

[0038] The methacrylic polymer (A) may contain a repeating unit derived from a polyfunctional monomer containing two or more radically polymerizable functional groups in one molecule within a range that allows the effects of the present invention to be obtained, thereby improving the solvent resistance, chemical resistance, etc.

[0039] The radical polymerizable functional group is not particularly limited as long as it has a carbon-carbon double bond and is radically polymerizable.Specific examples include vinyl group, allyl group, (meth)acryloyl group, (meth)acryloyloxy group, etc.In particular, (meth)acryloyl group is preferred from the viewpoint of excellent storage stability of the compound having the radical polymerizable functional group and easy control of the polymerizability of the compound. Here, "(meth)acryloyl" means at least one selected from "acryloyl" and "methacryloyl." The same applies to "(meth)acrylate" described below. In addition, each radically polymerizable functional group in a polyfunctional monomer containing two or more radically polymerizable functional groups may be the same or different.

[0040] Examples of the polyfunctional monomer include allyl methacrylate, allyl acrylate, ethylene glycol di(meth)acrylate, ethylene glycol tri(meth)acrylate, neopentyl glycol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate, but are not limited thereto. These may be used alone or in any combination of two or more in any ratio. Among these, the polyfunctional monomer is more preferably at least one selected from the group consisting of ethylene glycol di(meth)acrylate and neopentyl glycol di(meth)acrylate, and even more preferably ethylene glycol di(meth)acrylate, from the viewpoint of improving the solvent resistance and chemical resistance.

[0041] [Acrylic multi-layer particle structure polymer (B)] The acrylic multilayer particle structure polymer (B) according to this embodiment is a powdery acrylic polymer having a multilayer structure, characterized in that it contains a coagulated body of the acrylic multilayer particle structure polymer latex (C) emulsion-polymerized under a pH range of more than 9.0 and less than 14.0. The acrylic multilayer particle structure polymer (B) according to this embodiment is a single-dispersion acrylic multilayer particle structure polymer (B) having only one peak in the particle size distribution and small variation in particle size.

[0042] The acrylic multi-layer particle structure polymer (B) is not particularly limited as long as it is an acrylic polymer having the above multi-layer structure, but it is preferable that at least one inner layer has a layer of a rubber-like elastic body (soft polymer), and the outermost layer has a layer of a hard polymer. The acrylic multi-layer particle structure polymer (B) may have a multi-layer structure of three or more layers, including these inner layer, outermost layer, intermediate layer, and innermost layer. Specific examples of the structure include a two-layer structure having the soft polymer layer as an inner layer and the hard polymer layer as an outermost layer; a three-layer structure having the hard polymer layer as an innermost layer, the soft polymer layer as an intermediate layer and the hard polymer layer as an outermost layer; and a four-layer structure having the soft polymer layer as an innermost layer (first layer), the hard polymer layer as a second layer, the soft polymer layer as a third layer and the hard polymer layer as an outermost layer (fourth layer).

[0043] In the acrylic multilayer particle structure polymer (B), the monomer composition constituting the soft polymer (rubber-like elastomer) forming at least one layer of the inner layer may, for example, be one containing 0.1 to 10 parts by mass of a graft crosslinking agent and 0.1 to 10 parts by mass of a polyfunctional crosslinking agent having at least two vinyl groups, relative to 100 parts by mass of a monomer mixture containing 70 to 99.9% by mass of an alkyl acrylate having an alkyl group with 8 or less carbon atoms and 0.1 to 30% by mass of a monofunctional monomer having one vinyl group copolymerizable therewith.

[0044] Specific examples of the alkyl acrylate having an alkyl group having 8 or less carbon atoms include methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, etc., which can be used alone or in combination of two or more. Among these, n-butyl acrylate is preferred.

[0045] The above-mentioned copolymerizable monofunctional monomer having one vinyl group specifically includes aromatic unsaturated monomers such as styrene, vinyltoluene, and α-methylstyrene, and methacrylic monomers such as phenyl methacrylate, naphthyl methacrylate, cyclohexyl methacrylate, and benzyl methacrylate, which may be used alone or in combination of two or more. Among these, styrene is preferred as a monomer for adjusting the refractive index.

[0046] The graft crosslinking agent is a compound having a plurality of functional groups, at least one of which has a different reactivity from the other functional groups. Examples of such graft crosslinking agents include allyl esters of acrylic acid, methacrylic acid, maleic acid, or fumaric acid, which can be used alone or in combination of two or more. Among these, allyl acrylate and allyl methacrylate are preferred.

[0047] The polyfunctional crosslinking agent having at least two vinyl groups has a plurality of functional groups having the same reactivity in the molecule. Examples of such polyfunctional crosslinking agents include 1,3-butanediol dimethacrylate and 1,4-butanediol diacrylate, which can be used alone or in combination of two or more kinds.

[0048] In the acrylic multilayer particle structure polymer (B), the monomer composition constituting the hard polymer forming the outermost layer may be, for example, a monomer composition containing 60 to 100 mass % of an alkyl methacrylate having an alkyl group having 4 or less carbon atoms and 0 to 40 mass % of another unsaturated monomer copolymerizable therewith.

[0049] Specific examples of the alkyl methacrylate having an alkyl group having 4 or less carbon atoms include methyl methacrylate, ethyl methacrylate, and n-butyl methacrylate. These may be used alone or in combination of two or more. Of these, methyl methacrylate is preferred.

[0050] Examples of other unsaturated monomers copolymerizable with the above-mentioned monomers include alkyl acrylates having an alkyl group having 8 or less carbon atoms, which are given as examples of monomers constituting the layer of the rubber-like elastomer, compounds given as specific examples of monofunctional monomers having one copolymerizable vinyl group, compounds given as specific examples of graft crosslinking agents, acrylonitrile, methacrylonitrile, etc. These may be used alone or in combination of two or more.

[0051] [Acrylic multi-particle structure polymer latex (C)] The acrylic multilayer particle structure polymer latex (C) according to this embodiment is characterized in that it is obtained by emulsion polymerization of the monomer components constituting the above-mentioned acrylic multilayer particle structure polymer (B) under conditions of a pH range of more than 9.0 and less than 14.0. In the present invention, carrying out emulsion polymerization under conditions of more than 9.0 and less than 14.0 means that the pH of the aqueous system used in emulsion polymerization is in the range of more than 9.0 and less than 14.0, as shown in the examples below. By carrying out emulsion polymerization under the conditions within the above-mentioned pH range, it is possible to obtain the effect of imparting excellent impact resistance to the resin composition of the present invention obtained by blending the acrylic multilayer particle structure polymer (B) containing the coagulated body of the obtained acrylic multilayer particle structure polymer latex (C) with the methacrylic polymer (A) while maintaining the transparency.

[0052] Although the details of the mechanism by which the above effects are obtained are not clear, it is thought to be as follows. That is, the acrylic multi-particle structure polymer in the acrylic multi-particle structure polymer latex (C) emulsion-polymerized under conditions of a pH range of more than 9.0 and less than 14.0 has one peak in its particle size distribution, and therefore the variation in particle size is small. As a result, it is presumed that when blended with the methacrylic polymer (A), the compatibility is excellent, the transparency of the resulting resin composition and resin molded product are good, and the effect of excellent impact resistance is fully exhibited. The particle size of the acrylic multilayer particle structure polymer in the acrylic multilayer particle structure polymer latex (C) is not particularly limited, but is preferably in the range of 50 to 2000 nm, particularly 70 to 1000 nm, with the peak of the particle size distribution being in the range of 100 to 400 nm, particularly 110 to 350 nm.

[0053] When the acrylic multilayer particle structure polymer (B) according to the present embodiment is composed only of a coagulated body of the acrylic multilayer particle structure polymer latex (C), the particle size and particle size distribution of the acrylic multilayer particle structure polymer in the acrylic multilayer particle structure polymer latex (C) correspond to the particle size and particle size distribution of the acrylic multilayer particle structure polymer (B).

[0054] The method for measuring the particle size distribution of the acrylic multi-particle structure polymer in the acrylic multi-particle structure polymer latex (C) or the acrylic multi-particle structure polymer (B) is not particularly limited, and examples thereof include a method using a particle size distribution measuring device CHDF3000 manufactured by Matec Applied Sciences, a laser diffraction particle size measuring device Mastersizer 3000 manufactured by Malvern Panalytical, and the like.

[0055] When the pH of the emulsion polymerization system is 9.0 or less, it is not possible to produce an acrylic multilayer particle structure polymer having a single peak in the particle size distribution, but rather, as shown in Comparative Example 1 described later, the particle size distribution will have two or more peaks and will vary greatly, and as a result, it is not possible to achieve both transparency and impact resistance in the resin composition obtained by blending these. The pH of the emulsion polymerization system may be as high as more than 9.0; however, making the pH excessively high is not preferable because it requires a large amount of a compound for adjusting the pH and also requires costs for making the production equipment alkali-resistant. Therefore, it is preferable to control the pH of the emulsion polymerization system in producing the acrylic multilayer particle structure polymer latex (C) to more than 9.0 and not more than 13.0, particularly more than 9.0 and not more than 2.0.

[0056] An example of a method for controlling the pH range of the emulsion polymerization system to more than 9.0 and less than 14.0 is to add a known pH adjuster to the emulsion polymerization system. The pH adjuster may be at least one compound selected from hydroxides, carbonates, and hydrogencarbonates of alkali metals or alkaline earth metals, that is, one or more compounds selected from the group consisting of hydroxides, carbonates, and hydrogencarbonates of alkali metals and hydroxides, carbonates, and hydrogencarbonates of alkaline earth metals. More specifically, examples of the pH adjuster include lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, lithium hydrogen carbonate, sodium hydrogen carbonate, and potassium hydrogen carbonate. Among these, from the viewpoint of ease of controlling the pH range, hydrogen carbonate is preferred, and among these, sodium carbonate is particularly preferred.

[0057] The amount of these pH adjusters to be added is not particularly limited as long as it is an amount capable of adjusting the pH in the emulsion polymerization system to more than 9.0 and less than 14.0. Usually, the amount is 0.03 to 1.0 part by mass, and particularly preferably about 0.04 to 0.7 part by mass, per 100 parts by mass of the solid content of the acrylic multilayer particle structure polymer latex (C). Here, "100 parts by mass of the solid content of the acrylic multilayer particle structure polymer latex (C)" corresponds to a total of 100 parts by mass of the raw material unit components, emulsifier, the pH adjuster, polymerization initiator, and other additives added to the emulsion polymerization system.

[0058] <Polymerization process> The acrylic multi-layer particle structure polymer latex (C) can be obtained as a latex of a polymer having a multi-layer particle structure by emulsion-polymerizing the monomer components of the above-mentioned monomer composition constituting the innermost layer, adding the monomer components of the monomer composition constituting the outer layer to the obtained polymer latex of the innermost layer, and then repeating the emulsion-polymerization of the monomer components of the monomer composition constituting the outer layer in the polymer latex from which the inner layer is formed, and finally emulsion-polymerizing the monomers constituting the outermost layer. The emulsion polymerization method used for forming the polymer of each layer to obtain such an acrylic multi-layer particle structure polymer latex (C) is not particularly limited, except that the pH in the emulsion polymerization system is adjusted to more than 9.0 and less than 14.0 by adding the above-mentioned pH adjuster as necessary, and any known method can be used.

[0059] The emulsifier used in the above-mentioned emulsion polymerization may be any of anionic, cationic, and nonionic emulsifiers, but anionic emulsifiers are preferred.As such anionic emulsifiers, for example, potassium oleate, sodium stearate, sodium myristate, sodium N-lauroylsarcosinate, dipotassium alkenyl succinate, and other carboxylates, sodium lauryl sulfate, and other sulfates, sodium dioctyl sulfosuccinate, sodium dodecylbenzenesulfonate, and sodium alkyl diphenyl ether disulfonate, and other phosphates, such as sodium polyoxyethylene alkyl ether phosphate, and other phosphates. In the above-mentioned Patent Document 2, a phosphate salt is used as an emulsifier in the emulsion polymerization system. However, since the phosphate salt remains in the multilayer particle structure polymer and may deteriorate the appearance when the resulting resin molded product is formed, it is preferable to use, as the emulsifier, the above-mentioned carboxylate salt, sulfate salt, or sulfonate salt other than the phosphate salt.

[0060] The amount of the emulsifier can be appropriately selected depending on the emulsifier used, the type and blending ratio of the raw monomer components, and the polymerization conditions, and can be, for example, 0.1 parts by mass or more, preferably 0.5 parts by mass or more, relative to 100 parts by mass of the raw monomer components. In addition, the amount of the emulsifier used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the raw monomer components in order to suppress the amount of the emulsifier remaining in the polymer.

[0061] Examples of the polymerization initiator used in the emulsion polymerization include peroxides such as benzoyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, and hydrogen peroxide, azo compounds such as azibisisobutyronitrile, persulfate compounds such as potassium persulfate and ammonium persulfate, perchlorate compounds, perborate compounds, and redox initiators consisting of a combination of a peroxide and a reducing sulfoxy compound. The redox initiator is preferably a combination of an organic peroxide, ferrous sulfate, a chelating agent, and a reducing agent, such as a combination of cumene hydroperoxide, ferrous sulfate, sodium pyrophosphate, and dextrose, or a combination of t-butyl hydroperoxide, sodium formaldehyde sulfoxylate (Rongalit), ferrous sulfate, and disodium dihydrogen ethylenediaminetetraacetate. The amount of these radical polymerization initiators to be added varies depending on the radical polymerization initiator and monomers used, but can be, for example, about 0.01 to 10 parts by mass per 100 parts by mass of the raw material monomer components.

[0062] In the above emulsion polymerization, in addition to the above emulsifier and polymerization initiator, various additives that are generally added in emulsion polymerization, such as a chain transfer agent and an ultraviolet absorber, can be used.

[0063] The mass ratio of the raw material monomer component / water is not particularly limited and can be, for example, about 1 / 1 to 1 / 5, and may be about 1 / 1.5.

[0064] In the emulsion polymerization, the raw material monomer components, the polymerization initiator, etc. can be added to the reaction system by known methods such as batch addition, divided addition, continuous addition, etc. In the emulsion polymerization, in order to smoothly proceed with the reaction, it is possible to employ a method of replacing the inside of the reaction system with nitrogen, a method of raising the temperature of the reaction system after the completion of the reaction in order to remove the remaining monomer, or a method of adding a catalyst such as iron.

[0065] The polymerization temperature in the above emulsion polymerization can be, for example, 30 to 120°C, and is preferably 50 to 100°C.

[0066] <Coagulation process> The acrylic multi-particle structure polymer (B) in the present invention can be obtained as a coagulated product obtained by coagulating the acrylic multi-particle structure polymer latex (C) obtained by the above-mentioned emulsion polymerization. The acrylic multilayer particle structure polymer (B) can be recovered as a coagulated product of the above-mentioned acrylic multilayer particle structure polymer latex (C) by various methods such as acid coagulation, salt coagulation, freeze coagulation, spray drying, etc. Coagulants used in the salt coagulation method include inorganic salts such as aluminum chloride, aluminum sulfate, sodium sulfate, magnesium sulfate, sodium nitrate, and calcium acetate, and calcium acetate is particularly preferred in order to suppress coloration of the resin composition containing the acrylic multilayer particle structure polymer (B) and its molded product. These are usually used as an aqueous solution. The concentration of the aqueous coagulant solution is preferably 0.1 to 20% by mass, more preferably 1 to 15% by mass. By keeping the concentration within the above range, the acrylic multilayer particle structure polymer (B) can be stably recovered, and yellowing of the obtained resin composition and its molded article can be suppressed.

[0067] The temperature when the acrylic multilayer particle structure polymer latex (C) is brought into contact with the aqueous coagulant solution is preferably 30 to 100°C. The acrylic multi-layer particle structure polymer (B) thus precipitated can be washed, dehydrated, and dried by various methods. If a lubricant such as silica gel fine particles is added to the dried acrylic multi-layer particle structure polymer (B), the acrylic multi-layer particle structure polymer (B) becomes less prone to blocking and is easier to handle.

[0068] <Mixing process> There is no particular limitation on the method for producing the resin composition of the present invention containing the acrylic multilayer particle structure polymer (B) and the methacrylic polymer (A) obtained as described above. For example, a mixed powder of the resin composition of the present invention may be produced by powder blending both polymers. However, it is preferable to produce the resin composition of the present invention by mixing the methacrylic polymer (A), the acrylic multilayer particle structure polymer (B) and other components to be blended as necessary, and heating and melting the mixture using, for example, an extruder. The heating temperature in this case may be equal to or higher than the melting temperature of the methacrylic polymer (A) and the acrylic multilayer particle structure polymer (B), and may be, for example, 200 to 300°C.

[0069] [Content of acrylic multi-particle structure polymer (B)] The content of the acrylic multilayer particle structure polymer (B) in the resin composition of the present invention is not particularly limited, but in order to make the impact resistance of the resulting resin composition more sufficient, it is preferably from 10 to 90 parts by mass, more preferably from 20 to 70 parts by mass, and particularly preferably from 25 to 70 parts by mass, per 100 parts by mass of the total of the methacrylic polymer (A) and the acrylic multilayer particle structure polymer (B). When the content of the acrylic multilayer particle structure polymer (B) is equal to or higher than the lower limit, the effect of improving impact resistance can be sufficiently obtained, and when the content is equal to or lower than the upper limit, the effect of having excellent rigidity can be sufficiently obtained.

[0070] [Other ingredients] In addition to the above-mentioned methacrylic polymer (A) and acrylic structural polymer (B), the resin composition of the present invention may contain known additives such as antioxidants, ultraviolet absorbers, light stabilizers, release agents, pigments, and dyes, if necessary. When the resin composition of the present invention contains these additives, the content thereof is preferably about 0.01 to 10.0 mass %, for example about 0.01 to 5.0 mass %, relative to the total mass (100 mass %) of the resin composition.

[0071] [Resin molding] The resin molded article of the present invention is obtained by molding the resin composition according to the embodiment of the present invention. By molding the resin composition, a resin molded article that maintains transparency and impact resistance can be obtained.

[0072] Examples of methods for molding the resin composition of the present invention include press molding, injection molding, gas-assisted injection molding, welding molding, extrusion molding, blow molding, film molding, blow molding, multi-layer molding, and melt spinning.

[0073] The resin molded article of the present invention is not particularly limited as long as it is a molded article containing the resin composition of the present invention, and may be a molded article consisting of only the resin composition of the present invention, or may be a composite molded article including a molded article portion consisting of a resin composition other than the resin composition of the present invention.

[0074] The shape of the resin molded product of the present invention is not particularly limited, but may be, for example, a plate-shaped resin molded product (resin plate) or a sheet-shaped resin molded product (resin sheet). The thickness of the resin molded product can be adjusted to any thickness, from a thick plate to a thin film, as necessary, and may be, for example, 1 to 30 mm.

[0075] The resin molded article of the present invention has excellent transparency and impact resistance and can be used in a wide range of applications. The use of the resin molded article of the present invention is not particularly limited, but it is used in many applications such as vehicle parts such as automobile parts, medical parts, toys, liquid containers, optical materials, signs, displays, decorative parts, building parts, paints, home appliance parts, and face plates of electronic devices, and is particularly preferably used for parts that require impact resistance and have translucency, such as automobile parts, toys, and home appliance parts. It can also be used as a soft film or a composite film with different materials. Even in such products, it has excellent transparency and impact resistance. EXAMPLES

[0076] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention. In the following, "parts" and "%" refer to "parts by mass" and "% by mass", respectively.

[0077] [Preparation of test specimens] <Preparation of resin molded body X1> The resin compositions obtained in the examples and comparative examples were dried overnight with hot air at 80°C, and then injection molded using an injection molding machine (model name: EC75SXIII-2A, manufactured by Toshiba Machine Co., Ltd.) at a molding temperature of 250°C and a mold temperature of 60°C to obtain test pieces of resin molded body X1 having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm.

[0078] <Preparation of resin molded body X2> The resin compositions obtained in the examples and comparative examples were dried overnight with hot air at 80°C, and then injection molded using an injection molding machine (model name: EC20PN-II, manufactured by Toshiba Machine Co., Ltd.) at a molding temperature of 250°C and a mold temperature of 60°C to obtain test pieces of resin molded body X2 having a length of 50 mm, a width of 50 mm, and a thickness of 3 mm.

[0079] [Evaluation method] <Impact resistance evaluation> As an index of impact resistance, the notched Charpy impact strength (kJ / m) of resin molded body X1 was measured at a temperature of 23°C using a digital impact tester (model name: DG-UB, manufactured by Toyo Seiki Seisakusho) in accordance with ISO 179-1. 2 ) was measured.

[0080] <Transparency evaluation> The yellowness of the resin composition was evaluated by measuring the yellow index (YI) value. The YI value was measured using a spectrophotometer (model name: SE-7700, manufactured by Nippon Denshoku Industries Co., Ltd.) at a temperature of 23°C in accordance with ISO17223 using the resin molded body X2. The smaller the YI value, the better the color.

[0081] [Example 1] <Production of Acrylic Multilayer Particle Structure Polymer Latex (C-1)> 236 parts of ion-exchanged water and 0.05 parts of sodium carbonate were placed in a five-neck flask equipped with a stirrer, a reflux condenser, a nitrogen inlet, a monomer addition inlet, and a thermometer. The initial pH of the aqueous system was 9.5. The pH of the system was measured using a pH meter. Next, the mixture was purged with nitrogen while stirring and heated to 80°C. 0.48 parts of Rongalit, 1.2 x 10 parts of ferrous sulfate, and -4 parts, disodium dihydrogen ethylenediaminetetraacetate 3.6 x 10 -4 0.04 parts of emulsifier (sodium dodecylbenzenesulfonate: Neopelex G-15 (Kao Corporation)) were added.

[0082] Next, 3 / 10 of a mixture of 11.7 parts of methyl methacrylate, 0.76 parts of n-butyl acrylate, and 0.06 parts of allyl methacrylate was added over 10 minutes and held for 15 minutes. After that, the remaining 7 / 10 of the mixture and 0.22 parts of an emulsifier (sodium dodecylbenzenesulfonate: Neoperex G-15) were added over 30 minutes and held for 1 hour to obtain the first stage innermost layer polymer.

[0083] Next, an aqueous solution of 0.234 parts of Rongalite dissolved in 10 parts of ion-exchanged water was added to the above-mentioned first-stage innermost layer polymer, and after holding for 15 minutes, a mixture of 12.8 parts of styrene, 55.9 parts of n-butyl acrylate, 0.7 parts of allyl methacrylate and 0.35 parts of emulsifier (sodium dodecylbenzenesulfonate: Neopelex G-15) was added dropwise over 3 hours, and the mixture was held for 2 hours to obtain a second-stage intermediate layer / innermost layer polymer.

[0084] Thereafter, an aqueous solution of 0.06 parts of Rongalite dissolved in 10 parts of ion-exchanged water was added to the above-mentioned second stage intermediate layer / innermost layer polymer, and the mixture was held for 15 minutes, after which a mixture of 3.8 parts of methyl methacrylate and 0.12 parts of n-butyl acrylate was added dropwise over 20 minutes, and the mixture was held for 1 hour to form a three-layer particle structure polymer of the third stage outermost layer / middle layer / innermost layer.

[0085] The solid content of the resulting acrylic multi-particle structured polymer latex (C-1) was 40.0%. The amount of sodium carbonate added was calculated to be 0.049 parts per 100 parts of the solid content of the resulting acrylic multi-particle structured polymer latex (C-1).

[0086] The particle size distribution of the acrylic multi-particle structure polymer (B-1) in this acrylic multi-particle structure polymer latex (C-1) was measured using a particle size distribution measuring device CHDF3000 manufactured by Matec Applied Sciences, and the particle size distribution was a single peak. FIG. 1 shows a chart of the particle size distribution of the acrylic multi-particle structure polymer latex (B-1).

[0087] <Recovery of acrylic multi-particle structured polymer (B-1)> In a stainless steel vessel, 290 parts of 5.0% calcium acetate aqueous solution was charged as a coagulant aqueous solution, and the temperature was raised to 70°C while stirring, and 290 parts of the acrylic multi-layer particle structure polymer latex (C-1) obtained above was added continuously over 10 minutes. The temperature was then raised to 90°C, maintained for 5 minutes, and cooled to room temperature to obtain a coagulated liquid. The obtained coagulated liquid was dehydrated (1800 rpm: 3 minutes) using a centrifugal dehydrator (manufactured by Tanabe Iron Works Co., Ltd., top discharge type, model number: O-20) while washing with ion-exchanged water, and then dried in a static dryer to obtain an acrylic multilayer particle structure polymer (B-1).

[0088] <Production of resin composition and resin molded product> 600 parts of the acrylic multilayer particle structure polymer (B-1) obtained above was blended with 400 parts of ACRYPET VH (manufactured by Mitsubishi Chemical Corporation, a methacrylic resin containing 95% or more MMA units) as the methacrylic polymer (A), and the mixture was melt-kneaded using a twin-screw extruder (PCM-30 (trade name), manufactured by Ikegai Corporation, L / D=25) with an outer diameter of 30 mmφ at a cylinder temperature of 240°C and a die temperature of 250°C to produce pellets of a resin composition. Subsequently, resin molded body X1 and resin molded body X2 were produced using the pellets, and the Charpy impact strength and yellow index (YI) were measured. The results are shown in Table 1.

[0089] [Example 2] In Example 1, the amount of sodium carbonate used in the production of the acrylic multilayer particle structure polymer latex (C-1) was changed to 0.3 parts, and the pH of the initial water system was set to 11.4. In the same manner as in Example 1, an acrylic multilayer particle structure polymer latex (C-2) and an acrylic multilayer particle structure polymer (B-2) were obtained, and a resin composition and a resin molded product were obtained in the same manner, and evaluated in the same manner. The amount of sodium carbonate added in this Example 2 was calculated to be 0.294 parts per 100 parts of the solid content of the resulting acrylic multilayer particle structure polymer latex (C-2). The particle size distribution of the acrylic multi-particle structure polymer (B-2) contained in the obtained latex was a single peak, being a single dispersion. FIG. 2 shows a chart of the particle size distribution of the acrylic multilayer particle structure polymer (B-2). Moreover, the measurement results of the Charpy impact strength and the yellow index (YI) are shown in Table 1.

[0090] [Comparative Example 1] In Example 1, the sodium carbonate used in the production of the acrylic multilayer particle structure polymer latex (C-1) was not added, and the pH of the initial aqueous system was set to 7.2, and the same procedure as in Example 1 was repeated to obtain an acrylic multilayer particle structure polymer latex (C-3) and an acrylic multilayer particle structure polymer (B-3). In the same manner, a resin composition and a resin molded product were obtained, and evaluated in the same manner. The particle size distribution of the acrylic multi-particle structure polymer (B-3) contained in the obtained latex had two peaks. FIG. 3 shows a chart of the particle size distribution of the acrylic multilayer particle structure polymer (B-3). Moreover, the measurement results of the Charpy impact strength and the yellow index (YI) are shown in Table 1.

[0091] [Comparative Example 2] In Example 1, the acrylic multilayer particle structure polymer (B-1) was not added, and only ACRYPET VH (a methacrylic resin containing 95% or more MMA units, manufactured by Mitsubishi Chemical Corporation) was used as the methacrylic polymer (A) to obtain a resin molded product in the same manner, and the Charpy impact strength and yellow index (YI) were measured in the same manner. The results are shown in Table 1.

[0092] [Table 1]

[0093] As is clear from Table 1, the acrylic multilayer particle structure polymers (B-1) and (B-2) obtained by emulsion polymerization at a pH of more than 9.0 and less than 14.0 were monodisperse with one peak in the particle size distribution, and the resin moldings made of the resin compositions of Examples 1 and 2 using these acrylic multilayer particle structure polymers (B-1) and (B-2) had high Charpy impact strength and excellent yellow index (YI). On the other hand, the acrylic multilayer particle structure polymer (B-3) obtained by emulsion polymerization at pH 7.2 had a large variation in particle size, and in Comparative Example 1 in which this acrylic multilayer particle structure polymer (B-3) was used, the Charpy impact strength was low and the yellow index (YI) was also insufficient. Moreover, in Comparative Example 2, in which the acrylic multilayer particle structure polymer (B) was not added, the Charpy impact strength was lower than that of Comparative Example 1. From these results, it is understood that, according to the present invention, when the acrylic multilayer particle structure polymer (B) is produced by emulsion polymerization in the pH range of more than 9.0 and less than 14.0, the particle size distribution is monodisperse with small variation in particle size, and therefore, the acrylic multilayer particle structure polymer (B) having excellent impact resistance improvement effect can be produced without impairing the inherent transparency of the methacrylic resin, and that by blending such an acrylic multilayer particle structure polymer (B) with the methacrylic polymer (A), a resin composition and a resin molded product having excellent transparency and impact resistance can be provided.

Claims

1. A resin composition comprising a methacrylic polymer (A) and an acrylic multilayer particle structure polymer (B), The resin composition, wherein the acrylic multilayer particle structure polymer (B) comprises a coagulated product of an acrylic multilayer particle structure polymer latex (C) emulsion-polymerized under a pH range of more than 9.0 and less than 14.

0.

2. 2. The resin composition according to claim 1, wherein the particle size distribution of the acrylic multi-particle structure polymer in the acrylic multi-particle structure polymer latex (C) has one peak.

3. 2. The resin composition according to claim 1, wherein the acrylic multilayer particle structure polymer latex (C) contains at least one compound selected from the group consisting of hydroxides, carbonates, and hydrogencarbonates of alkali metals or alkaline earth metals.

4. 4. The resin composition according to claim 3, wherein the content of the at least one compound selected from the group consisting of hydroxides, carbonates and hydrogencarbonates of alkali metals or alkaline earth metals is 0.03 parts by mass or more and 1.0 parts by mass or less per 100 parts by mass of a solid content of the acrylic multilayer particle structure polymer latex (C).

5. 5. The resin composition according to claim 4, wherein the at least one compound selected from the group consisting of hydroxides, carbonates and hydrogencarbonates of alkali metals or alkaline earth metals contains a hydrogencarbonate.

6. The resin composition according to claim 5, wherein the hydrogen carbonate contains sodium carbonate.

7. The resin composition according to claim 1, wherein the methacrylic polymer (A) contains 50 mass % or more of repeating units derived from methyl methacrylate.

8. A resin composition comprising a methacrylic polymer (A) and an acrylic multilayer particle structure polymer (B), A resin composition, wherein the particle size distribution of the acrylic multilayer particle structure polymer (B) has one peak.

9. A resin molded product obtained by molding the resin composition according to any one of claims 1 to 8.

10. An automobile member comprising the resin molded article according to claim 9.

11. A toy comprising the resin molded article according to claim 9.

12. A member for home appliances, comprising the resin molded article according to claim 9 .

13. a polymerization step of obtaining an acrylic multi-layer particle structure polymer latex (C) by emulsion polymerization under a condition of a pH range of more than 9.0 and less than 14.0; a coagulation step of coagulating the obtained acrylic multi-particle structure polymer latex (C) to obtain an acrylic multi-particle structure polymer (B); and kneading the obtained acrylic multilayer particle structure polymer (B) with the methacrylic polymer (A).

14. A method for producing a resin molded product, comprising producing a resin composition by the method for producing a resin composition according to claim 13, and molding the resulting resin composition.

Citation Information

Patent Citations

  • Emulsion polymerization of vinyl monomer

    JP1988221108A

  • Acrylic multilayer structure polymer powder, method for producing the same and methacrylic resin composition

    JP2007023242A